Partisipasi Umat Lingkungan St. Maria Mengunjungi Elisabet Terhadap Nyanyian Liturgi Ekaristi Di Paroki MDKS MALANG - Emmeria Tarihoran; Fiktus Suyanto (Jurnal Pelayanan Pastoral, 2021)
The participation of the people in liturgical chant requires awareness and activeness. Liturgical chant is an important part of helping people celebrate the liturgy because singing has an inseparable position in the Eucharistic liturgy. This research proposes to describe the participation of the people of St. Maria Mengunjungi Elisabeth in the chanting of the Eucharistic Liturgy. The method employed is a descriptive quantitative approach. The whole sample of 72 consisted of 35 males and 37 females. The data collection technique applied open and closed questionnaires. Data processing using F Percent and Scoring. The results obtained indicate that the participation in the liturgical chant is in a good category, with an average score of 3.96. Chanting participation in the ordinarium category was very good, with an average score of 4.21. Participation in the respondent psalm and the introductory scripture to the gospel shows the category very good with an average score of 4.24. In the field of self-assessment, the participation of the Eucharistic liturgical chanting showed a good category with an average score of 4.03. The awareness of the participation of the singing people from the beginning to the end of the Eucharistic song shows a good category, with a score of 3.66. The inhibiting factor is not knowing the song, the song is difficult, the song is not Praise Gratitude with a percentage of 56%. While the supporting factor, namely knowing the song is easy to know the song with a percentage of 43.66%. The overall conclusion regarding the participation of the people in the liturgical eucharistic chant in St. Maria Mengunjungi Elisabeth is in a good category, with an average score of 4.03.